2020
DOI: 10.1055/a-1132-6223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Genetics of Primary Hyperparathyroidism

Abstract: Calcium homeostasis is maintained by the actions of the parathyroid glands, which release parathyroid hormone into the systemic circulation as necessary to maintain the serum calcium concentration within a tight physiologic range. Excessive secretion of parathyroid hormone from one or more neoplastic parathyroid glands, however, causes the metabolic disease primary hyperparathyroidism (HPT) typically associated with hypercalcemia. Although the majority of cases of HPT are sporadic, it can present in the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 116 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…About 5% of PHPT occurs in the familial setting. Patients usually present with multiglandular involvement with an equal or male sex predominance 4,5,7,52. It has been reported that up to 25% of parathyroid hyperplasia are a manifestation of a familial syndrome 6,7.…”
Section: Familial Hyperparathyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…About 5% of PHPT occurs in the familial setting. Patients usually present with multiglandular involvement with an equal or male sex predominance 4,5,7,52. It has been reported that up to 25% of parathyroid hyperplasia are a manifestation of a familial syndrome 6,7.…”
Section: Familial Hyperparathyroidismmentioning
confidence: 99%
“…Patients usually present with multiglandular involvement with an equal or male sex predominance. 4,5,7,52 It has been reported that up to 25% of parathyroid hyperplasia are a manifestation of a familial syndrome. 6,7 Familial forms of PHPT include multiple endocrine neoplasia (MEN1, MEN2, MEN4), familial hypocalciuric hypercalcemia 1, 2, and 3 (FHH1, FHH2, FHH3), familial hypercalciuric hypercalcemia, neonatal severe HPT, hyperparathyroidism jaw tumor syndrome (HP-JT) and familial isolated hyperparathyroidism (FIH).…”
Section: Familial Hyperparathyroidismmentioning
confidence: 99%
“…Secondarily, the co-presence of gastric, duodenal, and pancreatic neoplasia, in the majority of neuroendocrine tumors (NETs), represents a syndromic consequence via a common genetic background in multiple endocrine neoplasia (MEN) syndrome that comes with an increased burden of disease due to synchronous or asynchronous neoplasms requiring multidisciplinary management [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This special issue has other important updates for us in endocrine oncology: on thyroid cancer [11] and hyperparathyroidism [12], medullary thyroid cancer [13], adrenal hyperplasias [14] and new technologies for the investigation of adrenocortical neoplasms [15], and finally on the medical treatment of gastrointestinal neuroendocrine neoplasms [16], a field that is maturing significantly, more than a century after secretin's discovery [5].…”
mentioning
confidence: 99%